Internalization of Akhlakul Karimah Values Through Islamic Religious Education Learning for Class VII at MTs Misbahussibyan - Ai Siti Napisah; Diansyah Permana; Cecep Hilman (Annujum: Journal of Humaniora and Law, 2026)
The internalization of akhlakul karimah values through Islamic Religious Education learning is an important effort in shaping students’ character amidst the challenges of modern social development. This study aims to describe the implementation of Islamic Religious Education learning in internalizing akhlakul karimah values, explain the role of Islamic Religious Education teachers in instilling these values, and identify the supporting and inhibiting factors in the internalization process among seventh-grade students at MTs Misbahussibyan. This research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The results indicate that: (1) the internalization of akhlakul karimah values is carried out through Islamic Religious Education learning, religious habituation, advice, teacher role modeling, and religious school activities; (2) Islamic Religious Education teachers act as educators, mentors, motivators, supervisors, and role models in shaping students’ character; and (3) supporting factors include a religious school environment, habituation programs, teacher exemplarity, collaboration among teachers, and school support, while inhibiting factors include peer influence, uncontrolled social media use, lack of parental supervision, and differences in students’ characteristics. This study contributes to the development of Islamic Religious Education learning and student character-building programs in Islamic schools.